Pengaruh Formula Jamu Anti-Alergi Terhadap Kualitas Hidup Pasien Rinitis Alergi di Klinik Hortus Medicus Tawangmangu - Fajar Novianto; Zuraida Zulkarnain; Agus Triyono; Danang Ardiyanto; Ulfa Fitriani; Ulfatun Nisa; Peristiwan Ridha Widhi Astana; Setyo Sri Rahardjo (JURNAL ILMU KEFARMASIAN INDONESIA, 2021)
Allergies are health problems that can aﬀect a person’s quality of life. It is currently unknown whether the use of anti-allergic herbs can improve the quality of life for allergic patients. The purpose of this study was to determine the eﬀect of giving anti-allergic herbs on the quality of life of patients with allergic rhinitis at the Tawangmangu Hortus Medicus Clinic. The design of this research was a pre-post treatment quasi experimental. A total of 55 subjects were given anti-allergic herbal decoction consisting of sembung, javanese chilies, ginger, and nut grass for 4 weeks and drunk 3 times a day. Before the study and on day 28th, the subjects were examined for quality of life using the Short Form-36. The results were analyzed using the Wilcoxon test. The results showed that there was a signiﬁcant increase in quality of life between before and after drinking anti-allergic herbal medicine (p<0.05), especially for the dimensions of physical function, energy and general health. The conclusion is that anti-allergic herbs can improve the quality of life for allergic rhinitis patients.